All in Sync: how music and art are revitalizing American religion - Wuthnow, Robert (University of California Press, 2003)
Annotation, Nationally-known sociologist Robert Wuthnow studies the relationship between art and American religion, documenting the strong, positive relationship between participation in the arts and the burgeoning interest in spiritual growth